Synchronous triple primary gastrointestinal malignant tumors treated with laparoscopic surgery: A case report - Jiang Wei; Zhang Genshan; Li Haijie; Xu Xiangshang; Jia Lingwei; Luo Xuelai; Cao Zhixin (Open Medicine, 2023)
Synchronous gastrointestinal multiple primary tumors including gastric, colonic, and rectal cancers are rare. Moreover, it was a challenge to find an appropriate procedure without negatively impacting the overall outcome. We described the case of a 63-year-old woman who presented with a 4 month history of upper abdominal pain, acid regurgitation, and anemia. Gastroscopy with biopsy suggested early cancer of gastric antrum. Abdominal contrast-enhanced computerized tomography and colonoscopy revealed ascending colon and rectum tumors. She had no family history of malignancy. Endoscopic submucosal dissection was performed for gastric cancer, and the pathological result presented that it was poorly differentiated and invaded into deep submucosa. The laparoscopy-assisted radical surgery combined with distal gastrectomy, right hemicolectomy, and anterior resection of rectum was performed for these three tumors via eight ports and a 7 cm midline upper-abdominal incision. No other perioperative complications were encountered except postoperative ileus. The patient was discharged on the 12th postoperative day. The pathological results revealed gastric cancer (T1N0M0), right colonic cancer (T3N1M0), and rectal cancer (T2N0M0), indicating complete surgical resection. We reported that our laparoscopic approach for synchronous triple primary gastrointestinal malignant tumors was feasible and minimally invasive.